Integrated Reporting and Corporate Performance: Empirical Evidence of The IIRC Framework Adoption - Affan, Muhammad Wildan (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
Sustainability and transparency issues are becoming trending in the nature of corporate reporting. Stakeholders are accused to bring together all financial and nonfinancial metrics into one integrated report. The purpose of this study is to determine the effect of integrated reporting toward corporate performance. Integrated reporting measurement uses the construct adopted from IIRC. The research sample in this study is basic and chemical industry sector that listed in the Indonesia Stock Exchange in 2017. The reason in choosing those industries as a research subject is because the basic and chemical industry sector is recorded as a high growth industry sector in 2017. This study uses a linear regression as an analysis tool. This study concluded that integrated reporting has significant effect toward corporate performance.